Profil Fisik Calon Mahasiswa Baru Pendidikan Jasmani Universitas PGRI Adi Buana Surabaya - Mulyono, Mulyono (SATRIA : Journal of Sports Athleticism in Teaching and Recreation on Interdisciplinary Analysis, 2020)
Physical profiles of Student Physical Education candidates for the University of PGRI Adi Buana Surabaya. Research on prospective students for the Physical Education Study Program, Faculty of Pedagogy and Psychology batch III. The study aims to determine the level of physical condition of students candidate of the Physical Education departmen Study Program for the 2018-2019 academic year. This is an observational study with data sourced from the results of physical tests in the form of sit ups, push ups, agility tests and endurance tests for new student candidates for the 2018-2019 academic year in the Physical education study program, PGRI Adi Buana University, Surabaya. The test result data will then be analyzed using the SPSS program and after that the results of the research are interpreted. Based on the statistical results that in general the ability of the physical condition of the prospective students of the Physical Education program is in the low category, this can be proven by the T score study which shows the results of the sit-up test with a score of 6 push-up test results with a score of 7.93 agility test results with a score 3.72 and endurance test results with a score of 8.84.